2023
DOI: 10.3390/nu15030520
|View full text |Cite
|
Sign up to set email alerts
|

Pandemic-Era WIC Participation in Wilmington, Delaware: Participants’ Experiences and Challenges

Abstract: Special Supplemental Nutrition Program for Women, Infants, and Children (WIC) participants faced unprecedented challenges during the coronavirus disease 2019 (COVID-19) pandemic including financial concerns, a national infant formula shortage, and rising food costs. To mitigate these challenges, the United States Department of Agriculture implemented WIC program waivers and flexibilities aiming to simplify program operations (e.g., remote appointments and food package substitutions). However, little is known a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…Preliminary research found that the shortage increased stress, and some women even reported panic attacks. 39,42 The findings from this study emphasize the importance of nurses and other lactation professionals using reflexive listening to support their postpartum patients and considering their mental health when making recommendations about infant feeding. 43 Implementing universal patient-centered and trauma-informed care into lactation care is considered best practice and may help mitigate the effects of stress and allow patients to feel respected and like they have autonomy in their feeding decisions.…”
Section: Discussionmentioning
confidence: 82%
See 3 more Smart Citations
“…Preliminary research found that the shortage increased stress, and some women even reported panic attacks. 39,42 The findings from this study emphasize the importance of nurses and other lactation professionals using reflexive listening to support their postpartum patients and considering their mental health when making recommendations about infant feeding. 43 Implementing universal patient-centered and trauma-informed care into lactation care is considered best practice and may help mitigate the effects of stress and allow patients to feel respected and like they have autonomy in their feeding decisions.…”
Section: Discussionmentioning
confidence: 82%
“…Another study found that WIC participants were not clear on the substitution options and could not benefit from them. 39 In future emergencies, it will be important to ensure that communication about changes in WIC benefits be clear and shared in participants' native languages. In addition, it may be helpful for providers to consider availability of products in their recommendations about formula type.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations